A Cross-Sectional Study of Tampering in Xtampza ER, an Abuse-Deterrent Formulation of an Extended-Release Opioid, in a Treatment Center Population - Jewell, Jennifer; Black, Joshua; Ellis, Matthew; Olsen, Heather; Iwanicki, Janetta; Dart, Richard (Clinical drug investigation, 2023)
Background and Objective While the current landscape of opioid use disorder (OUD) is complicated by the increase in use of non-prescription opioids, prescription opioids continue to be frequently used in non-medical ways. In response to this abuse, pharmaceutical companies have developed abuse deterrent formulations (ADFs) for extended-release (ER) opioids. To test the effectiveness of Xtampza ER ADF (oxycodone myristate) at reducing tampering, its rate of tampering in a treatment-center population was compared to immediate release (IR) single entity (SE) oxycodone, other ER oxycodone opioids, and ER oxymorphone. Methods Data were collected between the third quarter of 2018 and the third quarter of 2021 from individuals entering nationally distributed opioid treatment programs. To determine odds of tampering with Xtampza ER compared to each comparator, a logistic model was fit with a random intercept allowing for multiple drugs in each subject. Within-subject correlation was assumed to have a compound symmetric relationship. Results Overlap among the categories of drug tampering was high. Logistic regression analyses found that oxycodone myristate had lower odds of tampering when compared to both IR SE oxycodone (OR = 0.23 [95% CI 0.11, 0.50], p = 0.0002) and ER oxymorphone (OR = 0.30 [95% CI 0.14, 0.67], p = 0.0038). Oxycodone myristate was not significantly different from other ER oxycodone opioids (OR = 0.5 [95% CI 0.24, 1.03], p = 0.0612). These findings did not change when the estimates were adjusted for age and sex. Conclusions Drugs employing ADF technology may reduce the likelihood of tampering when compared to non-ADF formulations in a treatment-center population, which represents an opportunity for intervention in OUD among those still requiring pain management.